2018
DOI: 10.2217/hep-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

How Rap and its GEFs control liver physiology and cancer development. C3G alterations in human hepatocarcinoma

Abstract: Rap proteins regulate liver physiopathology. For example, Rap2B promotes hepatocarcinoma (HCC) growth, while Rap1 might play a dual role. The RapGEF, Epac1, activates Rap upon cAMP binding, regulating metabolism, survival, and liver regeneration. A liver specific Epac2 isoform lacking cAMP-binding domain also activates Rap1, promoting fibrosis in alcoholic liver disease. C3G (RapGEF1) is also present in the liver, but mainly as shorter isoforms. Its function in the liver remains unknown. Information from diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 79 publications
3
25
0
Order By: Relevance
“…Moreover, over-expression of p87C3G isoform is associated with chronic myeloid leukemia development [ 31 ]. Our previous genomic and transcriptomic studies using available human cancer databases indicated that C3G mRNA levels are increased in HCC compared to a normal liver [ 32 ]. Furthermore, HCC patients bearing somatic mutations and other genetic alterations in C3G gene showed lower survival [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, over-expression of p87C3G isoform is associated with chronic myeloid leukemia development [ 31 ]. Our previous genomic and transcriptomic studies using available human cancer databases indicated that C3G mRNA levels are increased in HCC compared to a normal liver [ 32 ]. Furthermore, HCC patients bearing somatic mutations and other genetic alterations in C3G gene showed lower survival [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous genomic and transcriptomic studies using available human cancer databases indicated that C3G mRNA levels are increased in HCC compared to a normal liver [ 32 ]. Furthermore, HCC patients bearing somatic mutations and other genetic alterations in C3G gene showed lower survival [ 32 ]. Although these data suggest an implication of C3G in HCC, it remains unknown whether C3G is a positive or negative regulator of HCC cellular properties.…”
Section: Introductionmentioning
confidence: 99%
“…Several proteins deregulated in human cancers have been shown to affect centrosomal division and ciliogenesis (Bettencourt-Dias and Glover, 2007; Nigg and Holland, 2018; Plotnikova et al, 2008; Wang and Dynlacht, 2018; Gonczy, 2015). C3G has been implicated in tumorigenesis, with higher as well as lower levels seen in different cancers (Che et al, 2015; Guerrero et al, 1998; Gutiérrez-Berzal et al, 2006; Hirata et al, 2004; Okino et al, 2006; Priego et al, 2016; Radha et al, 2011; Samuelsson et al, 2011; Sequera et al, 2018). The function of C3G in regulating centrosome division may be responsible for its deregulation being associated with tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear functions like chromatin remodeling and splicing are regulated by C3G (Shakyawar et al, 2017; Shakyawar et al, 2018). In a cell and tissue type dependent manner, C3G functions to either increase or decrease cell proliferation, and altered C3G levels are associated with human tumors and other disorders (Che et al, 2015; Guerrero et al, 1998; Gutiérrez-Berzal et al, 2006; Hirata et al, 2004; Ishimaru et al, 1999; Okino et al, 2006; Radha et al, 2011; Samuelsson et al, 2011; Sequera et al, 2018; Voss et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the number of inhibitors identified for Rap1 are limited and have not progressed into clinical trials thus far. The inhibitors that target the small GTPases or indirect strategies involving GEF inhibitors or GAP activators were reported to have promising results in laboratory studies, but not during clinical trials [119]. In recent years, a combined structure-based virtual screening and high throughput screening utilizing fluorescent guanine nucleotide exchange assays discovered SOS1 inhibitor, a Ras GEF enzyme [120].…”
Section: Therapeutic Potential Of Rap1 Signaling In Cancersmentioning
confidence: 99%